Water, wastewater, and stormwater infrastructure management - Grigg, Neil S. (Florida, United States : Taylor & Francis, 2012)
The second edition of a bestseller, this book discusses details the latest research on management practices for water and sewer capital facilities with an emphasis on infrastructure. It explores recent advances and highlights the technique asset management, which has received international acceptance and applies across various infrastructure sectors. It covers the components of asset management systems, including computer platforms and software packages, methods for condition assessment and ratings, risk-based decision support systems, decision making protocols, triple bottom line business cases, and new options for repair, rehabilitation, and replacement of buried pipe assets.
Contents: Urban Water Infrastructure for healthy cities Managing water system and services Asset management for urban water system Capital improvement planning and programming Engineering and construction for the infastructure life cycle Financial management for urban water systems High-Performance operation of water systems Risk management and disaster preparedness Maintenance and renewal of water infrastructure Information technology for water infrastructure legal and regulatory control on urban water systems
Includes bibliographical references.
Keywords: MUNICIPAL ENGINEERING